Betaine inhibits Toll-like receptor 4 responses and restores intestinal microbiota in acute liver failure mice - Qian Chen (Nature Portfolio, 2020)
Abstract Previous research has revealed that the gut microbiome has a marked impact on acute liver failure (ALF). Here, we evaluated the impact of betaine on the gut microbiota composition in an ALF animal model. The potential protective effect of betaine by regulating Toll-like receptor 4 (TLR4) responses was explored as well. Both mouse and cell experiments included normal, model, and betaine groups. The rat small intestinal cell line IEC-18 was used for in vitro experiments. Betaine ameliorated the small intestine tissue and IEC-18 cell damage in the model group by reducing the high expression of TLR4 and MyD88. Furthermore, the intestinal permeability in the model group was improved by enhancing the expression of the (ZO)-1 and occludin tight junction proteins. There were 509 operational taxonomic units (OTUs) that were identified in mouse fecal samples, including 156 core microbiome taxa. Betaine significantly improved the microbial communities, depleted the gut microbiota constituents Coriobacteriaceae, Lachnospiraceae, Enterorhabdus and Coriobacteriales and markedly enriched the taxa Bacteroidaceae, Bacteroides, Parabacteroides and Prevotella in the model group. Betaine effectively improved intestinal injury in ALF by inhibiting the TLR4/MyD88 signaling pathway, improving the intestinal mucosal barrier and maintaining the gut microbiota composition.